2021
DOI: 10.3390/ijms22158300
|View full text |Cite
|
Sign up to set email alerts
|

MiR-7-5p Is Involved in Ferroptosis Signaling and Radioresistance Thru the Generation of ROS in Radioresistant HeLa and SAS Cell Lines

Abstract: In cancer therapy, radioresistance or chemoresistance cells are major problems. We established clinically relevant radioresistant (CRR) cells that can survive over 30 days after 2 Gy/day X-ray exposures. These cells also show resistance to anticancer agents and hydrogen peroxide (H2O2). We have previously demonstrated that all the CRR cells examined had up-regulated miR-7-5p and after miR-7-5p knockdown, they lost radioresistance. However, the mechanism of losing radioresistance remains to be elucidated. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 53 publications
1
43
0
Order By: Relevance
“…These results show that plasma membrane status and lipid peroxidation enzyme activity are very important in oxidative stress resistance. overexpression of ALOX12 enhances ROS generation and amount of HNE, which is one of the lipid peroxidation by-products [116]. These results indicate that the CRR cells inhibit ferroptosis and show resistance from oxidative stress via decreasing mitochondrial function.…”
Section: Involvement Of Mitochondrial Dysfunction In Treatment-resistant Cancer Cellsmentioning
confidence: 74%
See 2 more Smart Citations
“…These results show that plasma membrane status and lipid peroxidation enzyme activity are very important in oxidative stress resistance. overexpression of ALOX12 enhances ROS generation and amount of HNE, which is one of the lipid peroxidation by-products [116]. These results indicate that the CRR cells inhibit ferroptosis and show resistance from oxidative stress via decreasing mitochondrial function.…”
Section: Involvement Of Mitochondrial Dysfunction In Treatment-resistant Cancer Cellsmentioning
confidence: 74%
“…For example, when ALOX was administrated into isolated mitochondria, cytochrome c release and ROS generation were observed [ 115 ]. Furthermore, it has been reported that ALOX expression was enhanced in CRR cells, and overexpression of ALOX12 enhances ROS generation and amount of HNE, which is one of the lipid peroxidation by-products [ 116 ]. These results indicate that the CRR cells inhibit ferroptosis and show resistance from oxidative stress via decreasing mitochondrial function.…”
Section: Involvement Of Mitochondrial Dysfunction In Treatment-resistant Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, lipid metabolism regulates lipid membrane composition. Repeated radiotherapy exposure to fractionated radiotherapy can generate cancer cell lines resistant to radiation [45]. Work has shown that in cervical cancer cells, upregulation of MiR-7-5p promotes radiotherapy resistance by silencing arachidonate 12-lipoxygenase (ALOX12) and other components of ferroptosis signaling, thus limiting radiotherapy efficacy [45].…”
Section: Therapeutic Opportunities To Enhance Radiotherapy Efficacy Via Ferroptosis Inductionmentioning
confidence: 99%
“…Repeated radiotherapy exposure to fractionated radiotherapy can generate cancer cell lines resistant to radiation [45]. Work has shown that in cervical cancer cells, upregulation of MiR-7-5p promotes radiotherapy resistance by silencing arachidonate 12-lipoxygenase (ALOX12) and other components of ferroptosis signaling, thus limiting radiotherapy efficacy [45]. Together, these data suggest that lipid metabolism can be therapeutically targeted to improve radiotherapy efficacy.…”
Section: Therapeutic Opportunities To Enhance Radiotherapy Efficacy Via Ferroptosis Inductionmentioning
confidence: 99%